2009
DOI: 10.1038/emboj.2009.344
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of a β2-adrenergic receptor—GluR1 signalling complex for localized cAMP signalling

Abstract: Central noradrenergic signalling mediates arousal and facilitates learning through unknown molecular mechanisms. Here, we show that the b 2 -adrenergic receptor (b 2 AR), the trimeric G s protein, adenylyl cyclase, and PKA form a signalling complex with the AMPA-type glutamate receptor subunit GluR1, which is linked to the b 2 AR through stargazin and PSD-95 and their homologues. Only GluR1 associated with the b 2 AR is phosphorylated by PKA on b 2 AR stimulation. Peptides that interfere with the b 2 ARGluR1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
149
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(161 citation statements)
references
References 74 publications
11
149
1
Order By: Relevance
“…Through such coupling, AKAP5 could bring PKA into close proximity with GPCRs and their effectors to regulate local cAMP signaling (17,18). ␤1AR and ␤2AR are the only GPCR that have, so far, been shown to form such a complex, which interacts with AKAP5 via SAP97 and PSD-95 (23,31). The ionotropic AMPA-type glutamate receptor subunit GluR1 also forms a PDZ motif-dependent complex with MAGUKs and AKAP5 (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Through such coupling, AKAP5 could bring PKA into close proximity with GPCRs and their effectors to regulate local cAMP signaling (17,18). ␤1AR and ␤2AR are the only GPCR that have, so far, been shown to form such a complex, which interacts with AKAP5 via SAP97 and PSD-95 (23,31). The ionotropic AMPA-type glutamate receptor subunit GluR1 also forms a PDZ motif-dependent complex with MAGUKs and AKAP5 (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…The b 2 receptor activation can stimulate the PKA-dependent phosphorylation of the GluR1 subunit of AMPAR associated with the b 2 receptor and then increase membrane GluR1 expression at postsynaptic sites (Joiner et al, 2010). Several studies have suggested that extinction that induces AMPAR trafficking is distinct in different brain areas.…”
Section: Mechanism That Underlies the Role Of Hippocampal Ne In The Pmentioning
confidence: 99%
“…Elegant studies by Hell and colleagues (26,27) have suggested that ACs are recruited into larger signaling networks that include ␤-adrenergic receptors, kinases, and ion channels. We have shown that AKAP79 functions to scaffold its cargo of signaling enzymes to synaptic AMPA receptors (9).…”
Section: Ampa Receptor-associated Ac Activity Is Mediated In Part By mentioning
confidence: 99%